A comparison of two molecular methods for diagnosing leptospirosis from three different sample types in patients presenting with fever in Laos. (September 2018) - Woods, K.; Nic-Fhogartaigh, C.; Arnold, C.; Boutthasavong, L.; Phuklia, W.; Lim, C.; Chanthongthip, A.; Tulsiani, S.M.; Craig, S.B.; Burns, M.-A.; Weier, S.L.; Davong, V.; et al.
Abstract: Objectives: To compare two molecular assays ( rrs quantitative PCR (qPCR) versus a combined 16SrRNA and LipL32 qPCR) on different sample types for diagnosing leptospirosis in febrile patients presenting to Mahosot Hospital, Vientiane, Laos. Methods: Serum, buffy coat and urine samples were collected on admission, and follow-up serum ∼10 days later. Leptospira spp. culture and microscopic agglutination tests (MAT) were performed as reference standards. Bayesian latent class modelling was performed to estimate sensitivity and specificity of each diagnostic test. Results: In all, 787 patients were included in the analysis: 4/787 (0.5%) were Leptospira culture positive, 30/787 (3.8%) were MAT positive, 76/787 (9.7%) were rrs qPCR positive and 20/787 (2.5%) were 16SrRNA/ LipL32 qPCR positive for pathogenic Leptospira spp. in at least one sample. Estimated sensitivity and specificity (with 95% CI) of 16SrRNA/ LipL32 qPCR on serum (53.9% (33.3%–81.8%); 99.6% (99.2%–100%)), buffy coat (58.8% (34.4%–90.9%); 99.9% (99.6%–100%)) and urine samples (45.0% (27.0%–66.7%); 99.6% (99.3%–100%)) were comparable with those of rrs qPCR, except specificity of 16SrRNA/ LipL32 qPCR on urine samples was significantly higher (99.6% (99.3%–100%) vs. 92.5% (92.3%–92.8%), p <0.001). Sensitivities of MAT (16% (95% CI 6.3%–29.4%)) and culture (25% (95% CI 13.3%–44.4%)) were low. Mean positive Cq values showed that buffy coat samples were more frequently inhibitory to qPCR than either serum or urine (p <0.001). Conclusions: Serum and urine are better samples for qPCR than buffy coat, and 16SrRNA/ LipL32 qPCR performs better than rrs qPCR on urine. Quantitative PCR on admission is a reliable rapid diagnostic tool, performing better than MAT or culture, with significant implications for clinical and epidemiological investigations of this global neglected disease.